Informality in the Metropolitan Zone of the Valley of Mexico (ZMVM): a spatial econometric and quantile error analysis - David Robles-Ortiz; Roberto Alejandro Ramírez-Silva (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2020)
The objective of this research is to analyze the behavior of the main causes of informality and its spatial relationship in the Metropolitan Zone of the Valley of Mexico (ZMVM). To achieve the target, we use the methodology of spatial econometrics, we propose a quantile error from a weight matrix (W). The results found show that neighborhood effects do not explain the informality within the ZMVM moreover, the education variable has a negative impact on informality. The originality of this work is the spatial econometric analysis of the spatial relationship in informality within the ZMVM. One of the main limitations of the present investigation is that it only covers 67% of the total ZMVM localities. The conclusion that emerges from this research is the educational factor is a crucial variable in the reduction of informality in the analyzed area and there is not strong evidence about contagion of informality between municipalities. It is recommended to focus efforts to analyze other metropolitan areas, which present the same problem of informality.JEL:C10, C21, J40.